Annual Summary of Weather Data for Parsons - 2020 - M. Knapp (Kansas Agricultural Experiment Station Research Reports, 2021)
This report includes the annual summary of precipitation and temperatures from 2020 at the research locations represented in the 2020 Southeast Research and Extension Center Agricultural Research Report.
Keywords: Southeast Kansas; experiment field; Parsons; Kansas weather; crop conditions